Is whole-body computed tomography the standard work-up for severely-injured children? Results of a survey among German trauma centers - Bayer, J; Reising, K; Kuminack, K; Südkamp, N. P; Strohm, P. C (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2015)
PURPOSE OF THE STUDY: Whole-body computed tomography is accepted as the standard procedure in the primary diagnostic of polytraumatised adults in the emergency room. Up to now there is still controversial discussion about the same algorithm in the primary diagnostic of children. The aim of this study was to survey the participation of German trauma-centres in the care of polytraumatised children and the hospital dependant use of whole-body computed tomography for initial patient work-up. MATERIAL AND METHODS: A questionnaire was mailed to every Department of Traumatology registered in the DGU (German Trauma Society) databank. RESULTS: We received 60,32% of the initially sent questionnaires and after applying exclusion criteria 269 (53,91%) were applicable to statistical analysis. In the three-tiered German hospital system no statistical difference was seen in the general participation of children polytrauma care between hospitals of different tiers (p = 0.315). Even at the lowest hospital level 69,47% of hospitals stated to participate in polytrauma care for children, at the intermediate and highest level hospitals 91,89% and 95,24% stated to be involved in children polytrauma care, respectively. Children suspicious of multiple injuries or polytrauma received significantly fewer primary whole-body CTs in lowest level compared to intermediate level hospitals (36,07% vs. 56,57%; p = 0.015) and lowest level compared to highest level hospitals (36,07% vs. 68,42%; p = 0.001). Comparing the use of whole-body CT in intermediate to highest level hospitals a not significant increase in its use could be seen in highest level hospitals (56,57% vs. 68,42%; p = 0.174). CONCLUSION: According to our survey, taking care of polytraumatised children in Germany is not limited to specialised hospitals or a defined hospital level-of-care. Additionally, there is no established radiologic standard in work-up of the polytraumatised child. However, in higher hospital care -levels a higher percentage of hospitals employs whole-body CTs for primary radiologic diagnostics in polytraumatised children.
Keywords: polytrauma; Multiple Trauma; Child Health Services; Humans; Child; Germany; lidé; Trauma Centers; služby zdravotní péče o dítě; dítě; Health Care Surveys; Tomography, X-Ray Computed; Německo; traumatologická centra; průzkumy zdravotní péče; počítačová rentgenová tomografie